Penyebaran, Populasi dan Perilaku Makan Ibis Karau (Pseudibis davisoni) di Sungai Mahakam, Kalimantan Timur - Imanudin; Sutrisno, Edy (Media Konservasi, 2002)
The white-shouldered ibis (Pseudibis davisoni) is on of waterbird species from Threskiornithidae family and is classified as endangered species, based on the document of Birds to Watch 11. This survey was conducted in August-September 2001 along the Mahakam River, East Kalimantan. The population were gauged by broad observation based on previous research. The population of white-shouldered ibis in Mahakam River were estimated to be 53 individuals. This species was mostly found feeding on the muddy riverbanks, sand and gravel banks. The birds roosted at tall trees such as Compasia tree, Coompassia sp. White-shouldered ibis shows four different feeding behaviour namely probing, pecking, flipping and gropping. Poaching, deforestation caused by illegal forest logging and forest fire are causing the declining population these birds.